Karakteristik Third Place dan Tipologi Kafe di Yogyakarta Kasus: Kawasan Karangwuni dan Sekitarnya - Talenta Nanda Sireki; Bambang Hari Wibisono (Diponegoro University, 2020)
Technology advancements tend to trigger the transformation of the characteristics of third place, especially in the forms of interactions and activities. This research is aimed to explore the third place characteristics, typology, spatial development, and identify factors that construct the typology of cafés as third place in Karangwuni sub-district and the area nearby (Karangwuni, Karanggayam, Karangasem Baru, Karangbendo, dan Karangmalang). The research method used in this study was a mix-method, with deductive-explorative approach using field observation and questionnaire to the visitor of café as a third place, which were opened during the period between 2016 to 2018, and located in Karangwuni area and the areas nearby. The results of this study shows that the characteristics of cafés in Karangwuni and the areas nearby as a third place are still in accordance with Oldenburg’s characteristics. However, it is also revealed that there have been shifts of the form of interactions and activities within the cafés space. Typology analysis showed that there are several types of cafés that match with the form of co-working space, and there are spatial trends in typology based on activity. Meanwhile, some factors constructing the typology have relation with space settings in determining the behaviors of the users.